Study of highly concentrated olive oil-in-water emulsions stabilized by palm-based nonionic surfactant - Lim, Hong Ngee; Kassim, Anuar; Huang, Nay Ming; Yarmo, Mohd Ambar; Yeong, Shoot Kian (Penerbit Universiti Kebangsaan Malaysia, 2009)
Rheological properties of highly concentrated oil-in-water (O/W) emulsions (HCEs), formed by mixing palm-based nonionic surfactant, C12E6 (HLB = 11.7, CMC = 25μM), water and olive oil volume fraction ≥78vol% were investigated. Samples with lower oil volume fraction (<85%) and surfactant concentration (<8%) exhibited polydispersity of broader droplet size distribution (DSD). In contrast, samples with higher oil volume fraction (>85%) and surfactant concentration (>8%) displayed monodispersity of narrower DSD. The average droplet size decreased with increasing oil volume fraction and surfactant concentration. All frequency sweep experiments exhibited higher G’ than G”, representing the predominantly elastic nature of HCEs. The crossover of the ascendant and descendant flow curves of HCEs with higher oil volume fraction (>85%) and surfactant concentration (>8%) implied a structural build-up that could give rise to very high stability. The high stability was confirmed through accelerated stability test at 40°C for three months.